Primary immature teratoma of the liver in an adult: Case report - Duong Thai Quang Nguyen, MD; Phong Thanh Nguyen, MD; Nam Hoang Nguyen, MD; Chien Cong Phan, MD (Radiology Case Reports, 2023)
Teratoma is an uncommon germ cell tumor and develops from at least 2 of the 3 germ cell layers: ectoderm, mesoderm, and endoderm. The origin of teratoma is primordial germ cells that migrate from the allantois to the gonadal ridges during embryogenesis. The teratomas can be intragonadal or extragonadal. Primary extragonadal teratoma is defined as if there is no evidence of a primary tumor in the testicles or ovaries. Common extragonadal sites include the anterior mediastinum, retroperitoneum, sacral region, and intracranial cavity. Primary intrahepatic teratomas are extremely rare, accounting for less than 1% of all teratoma cases. Hepatic teratomas are more common in children than in adults. We present a case of an immature primary hepatic teratoma in an adult woman.